Politik Hukum Dalam Mewujudkan Netralitas Aparatur Sipil Negara Ber-dasarkan Undang-Undang Nomor 5 Tahun 2014 Tentang Aparatur Sipil Negara Dalam Pemilihan Umum (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In implementing ASN policy and management based on the principle of one of them is the princi-ple of neutrality, in which neutrality is not taking sides with anyone and taking sides with anyone. In its implementation, there are many problems with ASN neutrality, which are caused by the in-tervention of political parties and political officials, and also there are weaknesses in regulations and also the absence of special rules governing the neutrality of ASN..This type of research can be classified as a type of normative research. In this study, the focus is to examine the level of synchronization of law and legal systematics. Source of data used secondary data consisting of primary legal materials, secondary legal materials, and tertiary le-gal materials, data collection techniques in this study with the literature review method, after the data collected and then analyzed to draw conclusions.In the politics of ASN regulation law, there are many weaknesses, including ASNs having the right to vote, weaknesses in the ASN neutrality monitoring agency, the interference of politi-cal officials with bureaucratic officials, and the ASN Law does not contain indicators of ASN vio-lations. Second, it should be necessary to re-examine the elimination of ASN's voting rights and elections and regional elections, strengthen the authority of KASN in oversight and recommend violations of ASN neutrality to the President and Civil Service Officers, and the rules regarding the neutrality of ASN should be contained in a special regulation that only regulates the neutrali-ty of ASN.Keywords : Politics of Law – Neutrality- State Civil Apparatus